Libya Economic Monitor, Summer 2022 - World Bank (Washington, DC, 2022)
Libya is struggling to cope with a trifecta of crises, including the civil conflict, the Coronavirus (COVID-19) pandemic and most recently, the impact of the Russia-Ukraine crisis. Notwithstanding the tempering of conflict intensity since 2021, the Libyan economy has been battered by the conflict. GDP per capita estimates in 2021 stood at about half of its value in 2010 before the start of the conflict. Since 2020, the population has been hit by multiple waves of the COVID-19 pandemic. The health system, already affected by a decade of conflict, has struggled to deliver the necessary access and quality of care amid a raging pandemic. While Libya has reported a marked decline in COVID-19 cases and deaths since March 2022, the vaccination rate remains low. In addition, food insecurity has worsened, precipitated by the Russia-Ukraine crisis and the resulting shortages and price increases for staple foods in the domestic market.